Effect of GA3, Waxing and Micro Perforated Bags on shelf Life and Selected Quality Attributes of Papaya Fruit - Mesfin G, Biniam; Bower, J P (Journal of Postharvest Technology, 2017)
Papaya fruit is characterized by a relatively short shelf-life. To extend the shelf-life and to investigate the effect of various postharvest  treatments on shelf-life and quality, a study was conducted on papaya (Carica papaya) cv. Hortus Gold. The treatments included gibberellic  acid (GA3), waxing and micro-perforated bags (MPB). Fruits were held at four different temperatures (5.5, 7, 10 or 22ºC). Percentage weight  loss (PWL), firmness, skin colour change and respiration rate were evaluated on a weekly basis during the storage period. Selected quality  attributes such as total soluble solids (TSS), titratable acids (TA), pH and sugar:acid ratio were also measured after storage. Based on the  colour change and softening days to ripen was determined. PWL, softening, yellowing and respiration rate increased irrespective of treatments  as the storage time and temperature was increased. MPB and waxing significantly (P
Keywords: GA; micro-perforated bags; papaya and waxing